2008
DOI: 10.1103/physrevb.78.024431
|View full text |Cite
|
Sign up to set email alerts
|

Internal spin-wave confinement in magnetic nanowires due to zig-zag shaped magnetization

Abstract: We perform broadband spin-wave spectroscopy on thin submicrometer-wide Ni 80 Fe 20 magnetic wires. Intentionally, we apply the in-plane magnetic field under an angle that is a few degrees off with respect to the in-plane hard-axis direction. In an intermediate field regime we find dipole-exchange modes that, as substantiated by micromagnetic simulations, reflect spin waves in intrinsically formed nanometer-wide channels along the wire. Interestingly, this phenomenon is not ruled by the outer boundary condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 23 publications
5
60
0
Order By: Relevance
“…[7][8][9][10] Low-dimensional ferromagnetic nanostructures are particularly interesting due to unique magnetic configurations. [11][12][13][14][15][16] In contrast to nanowires or dots, hollow nanotubes possess three independent geometrical parameters for the control of the magnetic properties via shape anisotropy, i.e., the length L, the inner radius r i and the outer radius r o . It has been predicted that the magnetization reversal via vortex wall formation and propagation might be more controlled in nanotubes compared to solid nanowires since in nanotubes the Bloch point structure is avoided.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Low-dimensional ferromagnetic nanostructures are particularly interesting due to unique magnetic configurations. [11][12][13][14][15][16] In contrast to nanowires or dots, hollow nanotubes possess three independent geometrical parameters for the control of the magnetic properties via shape anisotropy, i.e., the length L, the inner radius r i and the outer radius r o . It has been predicted that the magnetization reversal via vortex wall formation and propagation might be more controlled in nanotubes compared to solid nanowires since in nanotubes the Bloch point structure is avoided.…”
Section: Introductionmentioning
confidence: 99%
“…The self-focusing was attributed to the interference of the copropagating 1 st -and 3 rd -order modes and viewed as a potentially usable means for efficient transmission of microwave signals. 31,34 In addition, Bayer et al 37 and Topp et al 38 investigated spin-wave spectra of a magnetic waveguide inhomogeneously magnetized in the transverse direction. These studies indicated that the spin-wave spectra of a transversely-magnetized magnetic waveguide are largely dependent on the size, shape, and boundary circumstance and the equilibrium magnetization distribution of the waveguide, the geometry of the utilized antenna, etc.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 This capability is especially interesting for the study of SMPs that support magnetic states not normally allowed in macroscopic magnets. [14][15][16][17] A direct current (dc) SQUID is a superconducting loop, intersected by two Josephson junctions, and works as a flux-to-voltage transducer, i.e., the magnetic flux threading the loop modulates the voltage V across the junctions, with a period of the magnetic flux quantum 0 = h/2e (see, e.g., Ref. 18).…”
Section: Introductionmentioning
confidence: 99%